The effect of subsidizing continuous training investments : evidence from German Establishment Data - Görlitz, Katja [Verfasser] (My University, 2010)
"This paper evaluates the impact of a training voucher program on establishments' investments in further training. The voucher program that was implemented in the German federal state of North Rhine-Westphalia increased training incentives for employees in small and medium-sized establishments by reducing training costs by 50%. The estimation is based on a quasi-experimental research design exploiting variation across time, regions and establishment size. Using establishment data, I find that the share of establishments that invest in training increased by 4-6 percentage points. Training intensity and the educational structure of participants remained unaffected among those establishments investing in training." (Autorenreferat, BIBB-Doku)
Vorab veröffentlicht als "Ruhr Economic Papers ; 144", http://repec.rwi-essen.de/files/REP_09_144.pdf [Zugriff 29.9.2011]
Keywords: S 1.5.3 Betriebliche Weiterbildung; S 4.1 Finanzierungsquellen; S 3.2.1 KMU, Klein- und Mittlere Unternehmen; T 3.4 Befragung; T 3.5 Statistik; Betriebliche Weiterbildung; Bildungsgutschein; Auswirkung; Bildungsinvestition; Klein- und Mittelbetrieb; Weiterbildungsverhalten; Weiterbildungsangebot; Qualifikationsstruktur; IAB-Betriebspanel; Quantitative Angaben; 2001-2007